1982
DOI: 10.1002/ajpa.1330590304
|View full text |Cite
|
Sign up to set email alerts
|

Altitude and infant growth in Bolivia: A longitudinal study

Abstract: The growth of 79 healthy, well-nourished lowland (400 M) and highland (3600 M) Bolivian infants was analyzed in a longitudinal study through the first postnatal year. Compared to low altitude infants, the high altitude infants were found, by analysis of covariance controlling for size at the previous exam, to be significantly shorter at birth, 1 and 6 months, while they were significantly lighter only at birth and 1 year. Recumbent length gain was slower in the high altitude infants in the early months of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 6 publications
(4 reference statements)
5
43
0
1
Order By: Relevance
“…These analyses demonstrated that high altitude could result in a delay in liner growth of early childhood in Tibet, independent of various social and other factors operating through nutrition and disease. This consequences also confirmed previous findings in other child populations as white nonHispanic children of the United States and children in Bolivia and Ecuador (Haas et al, 1982;Leonard et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These analyses demonstrated that high altitude could result in a delay in liner growth of early childhood in Tibet, independent of various social and other factors operating through nutrition and disease. This consequences also confirmed previous findings in other child populations as white nonHispanic children of the United States and children in Bolivia and Ecuador (Haas et al, 1982;Leonard et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have showed that altitude is associated with reduced birth weight and reduced childhood growth among different population (Pawson, 1977;Beall, 1981;Haas et al, 1982;Yip, 1987;Yip et al, 1988;Leonard et al, 1995;Weitz et al, 2000;Weitz and Garruto, 2004). However, related studies among Tibetan children were limited and yielded highly varied results.…”
mentioning
confidence: 99%
“…Analyzing families, ethnicity, living place and altitudes of four Andean countries during -1998, Larrea (2002 found that the rate of growth retardation among children and adolescents was three times less in the best socioeconomic district than that in the worst socioeconomic district. The important contribution of poor socio-economic conditions to growth retardation at high altitude has been noted by studies in other populations (de Meer et al, 1995;Haas et al, 1982;Greksa 1986Greksa , 2006Stinson, 1982;Tripathy et al, 2007;Weitz et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…High altitude profoundly reduces birth weight by slowing fetal growth in the third trimester, rather than shortening gestation (37). Therefore it follows that high altitude presents a unique opportunity to identify the maternal genetic factors influencing birth weight and hence has been the subject of numerous studies over the past 30 years in residents of the Tibetan Plateau, the Andean Altiplano, and the North American Rocky Mountains (16,23,24,40,41,66,67). Historical accounts dating to the time of the Spanish conquest of South America chronicle the difficulty experienced by early Spaniards in reproducing at high altitude.…”
Section: B Amentioning
confidence: 99%